Muslim women’s perspectives on the barriers to sexually transmitted infections testing and diagnosis in Saudi Arabia - Alomair, Noura; Alageel, Samah; Davies, Nathan; Bailey, Julia V. (Frontiers in Public Health, 2023)
Background Muslim women are especially vulnerable to sexually transmitted infections (STI) and are at higher risk of under-detection. Evidence on the unique barriers to STI testing and diagnosis among Muslim communities is severely lacking. Understanding the complexity of accessing STI testing and diagnosis in Muslim communities is an area that requires further exploration. We aimed to explore the multilevel barriers to STI testing and diagnosis among Muslim women. Methods We conducted qualitative semi-structured interviews informed by the ecological model of health. This study took place in Riyadh Saudi Arabia in 2019 with women aged over 18. Data were analysed using reflexive thematic analysis. Results Twenty-eight women were interviewed from different ages, marital status, employment, and educational levels. Muslim women’s perceived barriers to STI testing and diagnosis included personal, socio-cultural, and service-level barriers. Lack of knowledge about STIs, denial, and underestimating the seriousness of infection and symptoms were among the many individual barriers to STIs testing and diagnosis. Religious views towards extramarital sex and negative views of people with STIs is a significant barrier to STI testing and diagnosis. Lack of patient confidentiality and providers’ judgement and mistreatment were also cited as barriers to seeking healthcare. Conclusion Barriers to STI testing and diagnosis exist on many levels including personal, socio-cultural, religious, and healthcare services, and at policy level. Multilevel interventions are needed to reduce the stigma of STIs and facilitate access to sexual health services among Muslims. It is our recommendation that policy and research efforts are directed to enhance trust in the doctor-patient relationship through better clinical training as well as implementing stricter regulations to protect patients’ confidentiality in healthcare settings.